Hierarki Nilai dan Analisis Sosio-Historis: Telaah Metodologi Tafsir Kontekstual Abdullah Saeed dan Implikasinya Di Indonesia - Arda, Ahmad Musyafa; Fazriyanti, Fazriyanti; Budiyanto, Nuraini; Syahid, Aang Ahmad; Rosa, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2026)
The interpretation of the Qur’an in the modern era faces challenges in maintaining the relevance of the sacred text within today’s social and cultural contexts. Abdullah Saeed, a contemporary Muslim scholar, offers a contextual approach to Qur’anic interpretation as an effort to bridge the gap between the textual meaning of the Qur’an and modern realities. This article aims to briefly explain Saeed’s concept and method of contextual interpretation and its implications for Qur’anic studies in Indonesia. Through a literature-based study of Saeed’s works and related research, it was found that the contextual approach emphasizes the importance of historical and sociological analysis, recognition of multiple textual meanings, and the application of a hierarchy of values in understanding the Qur’anic verses. This approach is considered capable of producing interpretations that are more open, humanistic, and relevant to contemporary issues such as human rights, gender equality, and religious pluralism. Therefore, Abdullah Saeed’s contextual interpretation can serve as a constructive alternative for the development of Qur’anic interpretation studies in the Islamic world, especially in Indonesia.